2020
DOI: 10.3390/pr8121569
|View full text |Cite
|
Sign up to set email alerts
|

Improving Ammonium Sorption of Bayah Natural Zeolites by Hydrothermal Method

Abstract: Natural zeolites are easily found and abundant in Indonesia. The natural zeolites are low-cost minerals; however, their ammonium sorption is poor. A hydrothermal method was applied to improve the ammonium sorption. Hydrothermal treatment times were varied 8, 24, and 32 h. The parent and hydrothermal treated samples were characterized by using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopes (FE-SEM), Fourier-transform infrared spectroscopy (FTIR), and nitrogen physisorption. Ammonium adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The result is aligned with another group that reported that Bayah natural zeolites were clinoptilolite dominant type, which was applied for converting glycerol to glycerol carbonate [19]. However, the present work's dominant zeolite phase is different from our previous investigation, which identi ed that Bayah natural zeolites were mordenite dominant type [20]. The diffraction pattern of natural zeolites was varied even samples obtained from the same mining district due to uncontrolled conditions during the zeolite synthesis in nature [21].…”
Section: Natural Zeolites Characterizationsupporting
confidence: 85%
“…The result is aligned with another group that reported that Bayah natural zeolites were clinoptilolite dominant type, which was applied for converting glycerol to glycerol carbonate [19]. However, the present work's dominant zeolite phase is different from our previous investigation, which identi ed that Bayah natural zeolites were mordenite dominant type [20]. The diffraction pattern of natural zeolites was varied even samples obtained from the same mining district due to uncontrolled conditions during the zeolite synthesis in nature [21].…”
Section: Natural Zeolites Characterizationsupporting
confidence: 85%
“…Figure 6 presents the SEM images of the parent and recrystallized samples at 170 o C. At the magnification of 3500×, the needle-like sharp fibres appeared and increased in numbers in the ZT 170 (pointed by the arrow) when compared to the Na-parent zeolite. The typical form of natural zeolite mordenite is a needle [34], and the SEM images clearly demonstrate the increasing amount of zeolite mordenite for the recrystallized samples (ZT 170). The H-Parent sample did not clearly show a needle-shaped crystal shape like the typical form of recrystallized natural zeolites.…”
Section: Morphology and Elemental Compositions Of Hydrothermally Modi...mentioning
confidence: 94%
“…A prolonged hydrothermal process might also completely convert the initial mordenite phase into other unwanted phases. Conversion of the mordenite phase into other phases is also affected by temperature and NaOH concentration [33,34].…”
Section: Characteristics Of Bayah Natural Zeolitesmentioning
confidence: 99%
“…In this case, the commercial and environmental use of zeolite is almost unlimited. Zeolite can be applied to adsorption (Neolaka et al, 2017;2018;Kurniawan et al, 2020), ion exchange, and catalyst processes (Hudiyono et al, 2012;Kusuma et al, 2013;Yulizar et al, 2016;Król and Mozgawa, 2019). The adsorption process gained is a promising method for a long-term treatment and economically proven (Ariffin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%